Late Holocene range collapse in a former British seabird species. (7th April 2014) - Brace, Selina; Barnes, Ian; Kitchener, Andrew C.; Serjeantson, Dale; Turvey, Samuel T.; Stewart, John
Abstract Aim To determine the taxonomic identity of zooarchaeological gadfly petrel (Pterodroma) specimens from northern Europe, in order to investigate whether an unknown, now‐extinct Pterodroma species formerly occurred in this region, or whether extant north‐east Atlantic gadfly petrel populations now restricted to the Macaronesian Islands formerly had a much wider Holocene distribution. Location Zooarchaeological Pterodroma material from the Hebrides, Scotland, was compared with modern‐day material from the Madeira and Cape Verde archipelagos (Macaronesia) and a global Pterodroma sample. Methods We employed techniques for ancient DNA analysis to amplify mitochondrial cytochrome b sequence data from an Iron Age Scottish Pterodroma specimen. Bayesian phylogenetic analyses were applied to assess the phylogenetic relationship between these ancient sequence data and extant Pterodroma taxa. Results The Scottish Pterodroma sample is phylogenetically distinct from living Macaronesian populations and from all other extant Pterodroma taxa. Although it is phylogenetically placed outside any single Macaronesian taxon, it is most closely related to the P. feae–deserta complex, and the level of sequence divergence between the Scottish Pterodroma and Macaronesian populations is lower than that observed between any two extant global Pterodroma taxa. The extinct north Atlantic gadfly petrels are therefore not distinct at the species level from these surviving populations, and instead form part of the young evolutionary radiation represented today by recently divergent Pterodroma populations on Bugio and Cape Verde, which can all be interpreted as conspecific. Main conclusions Our results suggest that surviving Macaronesian P. feae–deserta populations represent the final remnant of a wider Holocene distribution of this species complex, with the Madeira and Cape Verde archipelagos constituting the final sanctuary of Pterodroma in the north Atlantic following late Holocene extirpation of more northerly colonies possibly associated with human‐mediated invasive mammal introduction across northern Europe. Macaronesia may therefore constitute a 'museum' of diversity rather than a 'cradle' of evolution for Atlantic Pterodroma.